Incidence of Zika virus infection in a prospective cohort of Belgian travellers to the Americas in 2016. (January 2019) - Huits, Ralph; Van Den Bossche, Dorien; Eggermont, Kaat; Lotgering, Erica; Feyens, Anne-marie; Potters, Idzi; Jacobs, Jan; Van Esbroeck, Marjan; Cnops, Lieselotte; Bottieau, Emmanuel
Highlights: Zika virus (ZIKV) incidence was studied in a prospective cohort of travellers. During the 2016 outbreak in the Americas, ZIKV incidence was 17% per month of travel. Only one of nine ZIKV cases (11%) was asymptomatic. Abstract: Background: The incidence rate of Zika virus (ZIKV) infection in travellers from non-endemic areas to the Americas during the ZIKV outbreak in 2016 is unknown. Methods: Belgian adults who planned to travel to South America, Central America, and the Caribbean were recruited prospectively to study the incidence and characteristics of ZIKV. Demographic data and sera were collected at baseline. Participants were trained to collect capillary blood on filter paper (BFP). When ill during travel, the participants completed a questionnaire and they sampled BFP for post-hoc analysis. All symptomatic participants were screened for ZIKV using ZIKV-specific RT-PCR on serum or urine, or BFP, and antibody detection assays (ELISA). Follow-up sera of asymptomatic travellers, obtained at least 20 days post travel, were tested by ZIKV ELISA only. All positive ELISA results were subject to confirmation by virus neutralization testing (VNT). Results: Forty-nine participants completed follow-up: 38 women and 11 men, with a median age of 32 years (range 19–64 years). Travel destinations were countries in South America ( n  = 20), Central America ( n  = 24), and the Caribbean ( n  = 5). The total travel duration was 67.8 person-months. Illness was reported by 24 participants (49.0%). ZIKV infection was confirmed in nine cases, by RT-PCR ( n  = 5) and by VNT ( n  = 4). Only one of nine ZIKV cases (11.1%) was asymptomatic. The ZIKV incidence rate was 17.0% (95% confidence interval 7.8–32.2%) per month of travel. Conclusions: The ZIKV incidence rate in adult travellers from non-endemic countries to the epidemic territories during the 2016 outbreak was high. Asymptomatic ZIKV infection was rare in this population.